Surf zone zooplankton temporal dynamics and their environmental regulation in a southwestern Atlantic sandy beach (Pehuen Co, Argentina) - Baleani, Carla Alejandra (2020)
Temporal dynamics of a zooplankton community were examined in the surf zone of Pehuen Co beach (PC), Argentina. The effect of environmental variables on the zooplankton composition and abundance was also investigated. Samples were obtained monthly between December 2016 and November 2017 from a fixed site during low tide. In all, 37 taxa were representative of the community. Meroplankton represented 59.45% of the total taxa, whereas holoplankton reached 40.54%. Five species were dominant: Acartia tonsa in summer months (2032 ind. m−3 in March), Paracalanus parvus and Ctenocalanus vanus in winter (4055 ind. m−3 and 264 ind. m−3, respectively, in July), and the sergestid Peisos petrunkevitchi (838.7 ind. m−3 in September) and the mysids Arthromysis magellanica (284 ind. m−3 in October) in spring. The highest total zooplankton abundances were registered in summer and winter, and the lowest ones were registered in autumn. The zooplankton community showed a strong seasonality, which can be mainly attributed to temporal changes in water temperature and to variations in suspended particulate matter (SPM), particulate organic matter (POM), and chlorophyll-a (Chl-a). Our results show that the zooplankton community structure was also affected by local variations in the velocity of the littoral current (VLC) and the wave height (WH). The present study shows that, besides seasonality, which seemed to be strong in this temperate region, other events affect zooplankton dynamics at a short-term time scale. Both VLC and WH are key factors that affect the zooplankton community structure in PC.